Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Kearsipan di SMKN 10 Surabaya - Rizky Desyana Qudsy; Durinda Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This study aims to determine the effect of the discovery learning model of student learning outcomes in archival subjects in SMKN 10 Surabaya. This research is a quasi-experimental research design experiments with a  form of nonequivalent control group design. This research was conducted at SMKN 10 Surabaya totaling 144 students. The sample in this study used students of class X OTKP 1 and X OTKP 2, both of whom had the same number of students as many as 36 students. The sampling technique used is non-probability sampling with purposive sampling types. The method in collecting data uses test, interviews, and documentation. This instruments used in this study used a syllabus, lesson plans, and pretest posttest sheets. Data analysis techniques in this study consisted of 2 parts including item analysis and analysis of student learning outcomes. Analysis of items including validity test, reliability test, the level of difficulty of questions, and dsitinguishing features. Where as in the analysis of student learning outcomes using homogeneity test, normality test, hypothesis testing, and gain score analysis. The results of this study prove that student learning outcomes in the cognitive domain increased by 86% in the experimental group compared to the control class with percentage 11%. Homogeneity test result produce P-Value (0,0854) > significance level (0,05), which means that a sample can be said to be homogeneous. When viewed from the t-test posttest shows ttable with a confidence level of 95% (âˆ=5%) and df=70 then produces tcount (9,961) > ttable (1,994), which indicates Ha accepted. When viewed from the t-test results showed the difference between pretest and posttest that tcount (15,838) > ttable (1,994), which indicates Ha accepted. So it can be concluded that there is an influence of discovery learning model on student learning outcomes in subjects archieves at SMKN 10 Surabaya.